Modelling and analysis of energy absorption capacity of 3D printed strcture design (C) - Ang, Nelly (Nanyang Technological University, 2022)
The purpose of this project is to design and analyse the energy absorbing capabilities of a unique auxetic lattice structure. An auxetic material is a special type of material whereby the Poisson’s ratio falls in the negative range. The behavior of these materials differs from regular materials in terms of characteristics like energy absorption and mechanical behavior. For that reason, it is important to have an in-depth study on these materials to allow for future applications on other engineering sectors. By designing and simulating the structures in Ansys Workbench, it is possible to evaluate on the capabilities of an auxetic material.